Perlindungan Hukum Terhadap Notaris/Ppat yang Berindikasi Melakukan Perbuatan Pidana (Studi Kausus Putusan Mahkama Agung Republik Indonesia Nomor 310 K/Pid.Sus/2022) - Nanjong, Melania Santa Inne (Universitas Ekasakti, 2023)
A notary is a public official whose authority is given by the state to carry out some government functions in terms of making authentic deeds. In carrying out their duties, notaries have the authority regulated in Law Number 30 of 2004 concerning the Position of Notaries which has been amended by Law Number 2 of 2014 concerning the Position of Notaries. A deed made by a notary is a product in which the contents of the deed contain formal data submitted by the person present, or in other words the contents of the deed are the wishes and/or wishes of the parties. The information submitted by these parties is not entirely true, because there are parties who submit false information for personal gain, which can harm or ensnare the notary in a criminal act. Losses resulting from the deed This can cause the notary to be sued by the injured party, or in other words the notary is deemed to have bad intentions, even though the notary has carried out his duties in accordance with what is regulated in the UUJN and the Notary's Code of Ethics and is considered to have committed a criminal act. What is the legal protection for the notary and what is the notary's responsibility for the deed.